The role of Programmed Death-Ligand 1 expression in nasopharyngeal carcinoma - Nadya Dwi Karsa; Sukri Rahman (Oto Rhino Laryngologica Indonesiana, 2020)
ABSTRACTBackground: Nasopharyngeal carcinoma (NPC) is a malignant tumor that arises from the epithelial cell that cover surface of the nasopharynx, which has the highest incidence of all types of head and neck cancer. Cell-mediated immunity plays an important role in the growth and development of NPC. The expressions of Programmed Death-Ligand 1 (PD-L1) of NPC is still being debated and researched. Objective: To find out and understand the role of PD-L1 expression in NPC. Literature review: PD-L1 is a ligand from Programmed Death-1 (PD-1) receptors that could be expressed by cancer cells. When the PD-1/PD-L1 pathway is active, it promotes survival of cancer cells via anti apoptotic signals and inhibits the activation of signaling pathways, which are critical for survival of T cells. Conclusion: Various studies had found an increase of the PD-L1 expression in NPC cancer cells. PD-L1 is also a potentially important tumor immunotherapy target and can be a significant prognostic factor in NPC. ABSTRAKLatar belakang: Karsinoma nasofaring (KNF) merupakan suatu tumor ganas epitelial nasofaring yang mempunyai insiden tertinggi di antara kanker kepala dan leher. Imunitas selular mempunyai peran penting terhadap pertumbuhan dan perkembangan KNF. Ekspresi Programmed Death-Ligand  1 (PD-L1) pada KNF masih diperdebatkan dan diteliti. Tujuan: Mengetahui dan memahami peran PD-L1 terhadap kejadian KNF. Tinjauan Pustaka: PD-L1 merupakan ligan dari reseptor Programmed Death-1 (PD-1) yang dapat diekpresikan oleh sel kanker. Jalur PD-1 / PD-L1 yang teraktivasi akan melindungi sel kanker melalui sinyal anti apoptosis dan menghambat aktivasi jalur-jalur pengiriman sinyal lain yang sangat penting untuk kelangsungan hidup sel T. Kesimpulan: Berbagai penelitian menemukan adanya peningkatan ekspresi PD-L1 pada sel kanker KNF. PD-L1 menjadi suatu target imunoterapi yang sangat penting dalam meningkatkan respon imun terhadap sel kanker dan dapat dijadikan suatu faktor prognosis pada KNF.